Reactive flows, diffusion and transport: from experiments via mathematical modeling to numerical simulation and optimization : final report of SFB (Collaborative Research Center) 359 - Jäger, Willi; Rannacher, Rolf; Warnatz, Jürgen (SpringerLink Bücher, 2007)
Mathematical Analysis for Transport-Reaction Systems -- Fluid Flows and Free Boundaries -- Nonlinear Evolution Equations and Applications -- Navier-Stokes Equations and Chemical Reactions -- Mesh and Model Adaptivity for Flow Problems -- Parallel Multigrid on Locally Refined Meshes -- Solving Multidimensional Reactive Flow Problems with Adaptive Finite Elements -- Optimization Methods for Reactive Flows -- Robustness Aspects in Parameter Estimation, Optimal Design of Experiments and Optimal Control -- Multiple Set Point Partially Reduced SQP Method for Optimal Control of PDE -- Adaptive Finite Element Methods for PDE-Constrained Optimal Control Problems -- Chemical Reaction Systems -- Determination of Kinetic Parameters in Laminar Flow Reactors. I. Theoretical Aspects -- Determination of Kinetic Parameters in Laminar Flow Reactors. II. Experimental Aspects -- Optimization of Reactive Flows in a Single Channel of a Catalytic Monolith: Conversion of Ethane to Ethylene -- Reaction Processes on Catalytically Active Surfaces -- Stochastic Modeling and Deterministic Limit of Catalytic Surface Processes -- Turbulent Flow and Combustion -- Multigrid Methods for Large-Eddy Simulation -- Modeling and Simulation of Turbulent Non-Reacting and Reacting Spray Flows -- Transport and Diffusion in Boundary Layers of Turbulent Channel Flow -- Diffusion and Transport in Accretion Discs -- Evolution of Protoplanetary Disks Including Detailed Chemistry and Mineralogy -- Numerical Methods for Multidimensional Radiative Transfer -- Flows in Porous Media -- Multiscale Analysis of Processes in Complex Media -- Microscopic Interfaces in Porous Media -- High-Accuracy Approximation of Effective Coefficients -- Numerical Simulation and Experimental Studies of Unsaturated Water Flow in Heterogeneous Systems -- Lake Dynamics: Observation and High-Resolution Numerical Simulation -- Computer Visualization -- Advanced Flow Visualization with HiVision -- VisuSimple: An Interactive Visualization Utility for Scientific Computing -- Volume Rendering in Scientific Applications.